1989
DOI: 10.1139/y89-251
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the canine pyloric sphincter in relation to function

Abstract: The ultrastructure and immunocytochemistry of the canine distal pyloric muscle loop, the pyloric sphincter, were studied. Cells in this muscle were connected by gap junctions, fewer than in the antrum or corpus. The sphincter had a dense innervation and a sparse population of interstitial cells of Cajal. Most such cells were of the circular muscle type but a few were of the type in the myenteric plexus. Nerves were sometimes associated with interstitial cell profiles, but most nerves were neither close to nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
1
26
2
Order By: Relevance
“…On the other hand, the second type of cell in the present study probably corresponds to fibroblast-like ICC (Daniel et al 1989) and shows close similarities to fibroblast-like cells in the DMP region of the guinea-pig small intestine (Zhou and Komuro 1992a, b) and the rat small intestine , although their gap junctions seem to be larger in size and number than those of the small intestine.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…On the other hand, the second type of cell in the present study probably corresponds to fibroblast-like ICC (Daniel et al 1989) and shows close similarities to fibroblast-like cells in the DMP region of the guinea-pig small intestine (Zhou and Komuro 1992a, b) and the rat small intestine , although their gap junctions seem to be larger in size and number than those of the small intestine.…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, it can be concluded that the first cell type, which is characterized by large gap junctions, abundant mitochondria, and a highly electron-dense cytoplasm conforms to ICC in the rat stomach, as previously suggested by evidence that ICC in the mouse small intestine express c-kit mRNA (Huizinga et al 1995) and that the myenteric ICC of the guinea-pig small intestine show immunoreactivity to anti-c-kit receptors . This first type of interstitial cell in the rat stomach appears to correspond to ICC of the dog stomach, which are described as having an electron-dense cytoplasm (Daniel et al 1984(Daniel et al , 1989, and also to ICC of the human stomach, which are characterized by abundant intermediate filaments (Faussone-Pellegrini et al 1989). …”
Section: Discussionmentioning
confidence: 94%
“…In addition, CCKAR-bearing ICC were located in two bands of circular muscle of terminal antrum origin, that rotated near the midventral and dorsal sides of the pylorus to join the sphincter muscle. These latter two bands of circular muscle could be regarded as the equivalent to the inner muscle loops in the guinea pig, which change direction to join the distal sphincter muscle (Cai and Gabella 1984) and the torus described in dogs and humans (Torgensen 1942;Schulze-Delrieu et al 1984;Daniel et al 1989). Thus, CCKAR-bearing ICC are limited to a specific region of the distal pyloric sphincter, where fibers of antral and duodenal origin fuse.…”
Section: Interstitial Cells Of Cajalmentioning
confidence: 99%
“…As regards its role as a muscle relaxant, there are many in vivo studies on the inhibitory actions of VIP on sphincters (for review, see Daniel, 1985). Indeed, a dense distribution of VIP-like imrnunoreactive nerves has been found in the sphincters of the gastrointestinal tracts of various mammals Daniel et aL, 1989;Gonda et aL, 1989). The dense distribution of VIP-like immunoreactive nerve fibres in the inner part of the inner muscle layer in the pyloric part tends to suggest that the ventriculopyloric orifice and the pyloric part itself constrict with a sphincter-like action and that the inner part of the inner muscle layer is the main contributor to this contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, numerous nerves with VIP-like immunoreactivity have been found in such sphincters Gonda et aL, 1989;Daniel et al, 1989). Many authors have examined the distribution of the VIP-like immunoreactive nerves in the gastrointestinal tract of birds (Sundler et al, 1979;Vaillant et aL, 1980;Fontaine-Perus et aL, 1981;Reinecke et aL, 1981_;Saffrey et aL, 1982;Epstein et al, 1983;Vittoria et al, 1992).…”
Section: Introductionmentioning
confidence: 99%